Analisis Efektivitas Pendistribusian Zakat Produktif Dalam Meningkatkan Kesejahteraan Mustahik Pada Laznas Wahdah Inspirasi Zakat Makassar - Nur Safitri; Muhammad Nasri Katman; Trisno Wardy Putra; Fathurrahman; Ayu Ruqayyah Yunus (Al-Musthofa: Journal of Sharia Economics, 2026)
The objectives of this study are: 1) to analyze the productive zakat distribution model at LAZNAS Wahdah Inspirasi Zakat, and 2) to analyze the effectiveness of productive zakat distribution in improving the welfare of mustahik (zakat recipients). This study employs a qualitative method with a phenomenological approach. The results indicate that: 1) the productive zakat distribution model at LAZNAS Wahdah Inspirasi Zakat comprises two programs: the micro-enterprise development program and the Gerobak Berkah (Blessed Cart) program. The micro-enterprise development program targets mustahik whose businesses are declining or have folded due to a lack of capital, whereas the Gerobak Berkah program is intended for mustahik who lack adequate business premises. Based on the application of management functions in the distribution process, both programs are operating effectively and clearly, thereby facilitating the growth of the mustahik's businesses. 2) The productive zakat distribution by LAZNAS Wahdah Inspirasi Zakat is considered effective in improving mustahik welfare, based on the effectiveness indicators proposed by Sutrisno. Following the receipt of productive zakat aid, mustahik experienced tangible improvements in their business operations, resulting in increased income.